(untitled) (Impulse: Journal of Research and Innovation in Physics Education, 2024)
This research aims to develop a physics module based on problem-based learning to improve high school students’ critical thinking skills in work and energy. The research also aims to evaluate the quality of the module and obtain student responses to its use. This research uses a 4D model, namely define, design, develop, and disseminate. The development stage only includes the development stage with extensive testing. There were 10 students randomly selected from classes XI Math and Science 2 and 4 for the limited trial phase, while 35 students from class XI Math and Science 3 for the extensive trial. The research instrument consists of a validation sheet, assessment sheet, and response questionnaire sheet. Module evaluation and student responses are presented in checklist form. The results of this research are: (1) producing a physics module based on a problem-based learning model to facilitate high school students critical thinking skills on the subject of work and energy, (2) the quality of the module that has been developed according to material experts, media experts and physics teachers is Very Good with the respective mean scores being 3.46, 3.58 and 3.74, and (3) the student’s response to the module being developed was Agree with the mean score on the limited trial being 0.97 and on the extensive trial being 0.90. Thus, the development of a physics module based on problem-based learning to facilitate high school students’ critical thinking skills on the subject of work and energy is suitable for use in physics learning.